High Temperature Tribological Performance of Steel/Copper Friction Pairs Lubricated with a Modified C-WS2-(Fe3O4 + TiN) Nanoadditives in Non-Copper Coated Solid Wires - Hong Li; Jing Zhu; Zisong Chen; Zhuoxin Li; Bo Meng (Nanomaterials, 2022)
In this study, four kinds of nanoparticles, graphite, WS2, Fe3O4, and TiN, were used as lubricating additives for steel/copper friction pairs to solve the problem of welding contact tube wear with non-copper-coated solid wire at high temperature. The single and composite nanoparticles have excellent dispersion stability in absolute ethanol under the action of the compound surfactant NaSTA + OA + PVP (i.e., sodium stearate, oleic acid, and polyvinylpyrrolidone). The tribological test results showed that the maximum decrement, with reference to the average coefficient of friction and wear volumes, were measured with nanoparticle concentration in 1:1:1 ratio at 300 °C. Compared with dry friction, the average friction coefficient and wear volume are reduced by 74.3% and 84.8%, respectively, which may be attributed to the formation of a stable tribo-film mainly composed of C–O, Fe2O3, WO3, TiO2, TiNxOy composite on the worn surface. Therefore, it is considered that the combined lubrication effects of the ball-bearing effect, repairing of worn surfaces, and the tribo-film resulted in the lowest friction and wear.